E3 Ubiquitin Ligase TRIP12 Controls Exit from Mitosis via Positive Regulation of MCL-1 in Response to Taxol - Kripa S. Keyan (17807771) (2023)
Chemotherapy resistance is a major hurdle in cancer treatment. Taxol-based chemotherapy is widely used in the treatment of cancers including breast, ovarian, and pancreatic cancer. Loss of function of the tumor suppressor F-box WD-40 domain containing 7 (FBW7) mutations leads to the accumulation of its substrate MCL-1 which is associated with Taxol resistance in human cancers. We recently showed that E3 ubiquitin ligase TRIP12 is a negative regulator of FBW7 protein. In this study, we find that Taxol-induced mitotic block in cancer cells is partly controlled by TRIP12 via its positive regulation of MCL-1 protein. Genetic inhibition of TRIP12 accelerates MCL-1 protein degradation in mitosis. Notably, introducing double-point mutations in lysines 404/412 of FBW7 to arginine which makes it resistant to proteasomal degradation, leads to the sharp reduction of MCL-1 protein levels and sensitizes cancer cells to Taxol-induced cell death. Finally, TRIP12 deletion leads to enhanced mitotic arrest and cell death in an FBW7 and MCL-1 dependent manner in multiple cell lines including colorectal and ovarian cancer but not in breast cancer. Thus, the TRIP12/FBW7/MCL-1 axis may provide a therapeutic target to overcome Taxol-associated chemotherapy resistance in cancer. Other Information Published in: Cancers License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/cancers15020505